Difusi Inovasi Manajemen Pembelajaran Dalam Bina Furudhul Ainiyah Lembaga I’dadiyah Pondok Pesantren Nurul Jadid - Nurul Rosita Putri Nurul; Moh. Rofiki (STKIP Al Islam Tunas Bangsa dan HEPI, 2023)
This research discusses bina furudhul ainiyah with the diffusion of innovations made in its learning management in I'dadiyah institutions, especially the Al- Hasyimiyah area of Nurul Jadid Islamic Boarding School. This research uses a qualitative approach with a case study type. Data sources consist of primary and secondary data. Primary data were obtained from research informants including teaching staff of I'dadiyah institutions, foster guardians of I'dadiyah institutions and some students, while secondary data were obtained from scientific journals both national and international. Data were collected through participant observation techniques, in-depth interviews, and documentation. The data analysis used a continuous participatory technique, through the stages of data collection, reduction, presentation, and conclusion drawing. The results of this study inform that the I'dadiyah institution of Nurul Jadid Islamic Boarding School implements organized learning management with group and inter-personal innovation diffusion in the form of bina furudhul ainiyah innovation intensively for three months. Furthermore, the diffusion of this innovation is very influential on the effectiveness of student learning, especially religious learning with a predetermined achievement target for three months and is able to give a positive impression and response by students.